City Dionysia: narrating wasteland in urban life. Issue 1 (2nd January 2023) - Arabindoo, Pushpa; Baldwin, Nicola
ABSTRACT: Using the centennial anniversary of TS Eliot's The Waste Land as an opportune moment to reconsider the reflexive and the discursive in addressing themes occupying critical and creative thought, this document discusses the collaboration between a social scientist and a playwright during and in the aftermath of the COVID-19 pandemic. Its main output, a play titled Wasteland, had an understory framed by the problem-event of the lockdown as it confronted not only the negativity of wasteland but also the possibility of negating it simultaneously. The play situates itself in the privileged UCL Student Centre to probe its 'storied matter' through repeated re-enactments. As an encounter between words and worlds across a temporal threshold marked by 'becoming-events', the play draws the building into focus, diffracting it, blurring it, and finally opening it up as a wasteland. Based on the Ancient Greek theatrical tradition of City Dionysia, it relies on 'preplays', multiple 'draft' readings, to emphasise less a staged performance and more an identity text that is unhurried, unfinished, improvised and provisional. For, in the inter-subjective exchanges within this text we find 'the sense of ongoingness' (Berlant 2008) to inhabit the now of our (post)pandemic present.